Combined effects of chronic PM2.5 exposure and habitual exercise on cancer mortality: a longitudinal cohort study. (11th October 2021) - Bo, Yacong; Yu, Tsung; Chang, Ly-Yun; Guo, Cui; Lin, Changqing; Zeng, Yiqian; Huang, Bo; Tam, Tony; Lau, Alexis K H; Wong, Samuel Y S; Lao, Xiang Qian
Abstract: Background: Exercise may increase the inhalation and deposition of air pollutants, which may counteract its beneficial effects. We thus examined the combined effects of chronic exposure to fine particulate matter (PM2.5 ) and habitual exercise on the risk of death from cancer in Taiwan. Patients and methods: A total of 384 128 adults (≥18 years of age) were recruited for a medical screening programme between 2001 and 2016, yielding 842 384 medical-examination records. All participants were followed up until 31 May 2019. Vital data were obtained from the National Death Registry of Taiwan and the ambient PM2.5 exposure was estimated using a satellite-based spatiotemporal model. Information on habitual exercise was collected using a standard self-administered questionnaire. The time-dependent Cox-regression model was used to evaluate the combined effects. Results: A greater amount of habitual exercise was associated with lower risk of death from cancer, whilst a higher level of PM2.5 exposure was associated with a higher risk of death from cancer. The inverse associations of habitual exercise with death from cancer were not modified by chronic exposure to PM2.5 . The participants in the group with a high level of exercise and a low level of PM2.5 exposure exhibited a 35% lower risk of death from cancer than those in the group with a low level of exercise and a high level of PM2.5 exposure (95% confidence interval: 28%, 42%). Conclusions: Increased levels of exercise and reduced exposure levels of PM2.5 are associated with a lower risk of death from cancer. Habitual exercise reduces the risk of death from cancer regardless of the levels of chronic PM2.5 exposure. Our results indicate that habitual exercise is a suitable health-promotion strategy even for people who reside in moderately polluted regions.